Description of the Safety Climate Using the NOSACQ-50 Method for Employees in the Production Section at Pt. X in 2021 - Willia Novita Eka Rini; Septiani Gracia (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study was to overview of the safety climate in PT X to improve safety in PT X. This study is a quantitative research with a cross sectional approach. Sample counts use the total sampling method with a total sample of 117. Most of respondents were young adults of male sex, and the higher education level with tenure status above 5 years. An overview of priority dimensions and management's commitment to safety is a “good” category with a mean value of 3, the dimension of empowerment of safety management is a “good” with a mean value of 3.1, safety management fairness dimensions is a “good” category with a mean value of 3.2, the dimensions of workers' commitment to safety is a “good” category with a mean value of 3.1, the priority dimensions of worker safety and not tolerated risk of hazards is a “bad” category with a mean value of 2.9, the dimensions of learning, communication and trust in colleagues is a “good” category with a mean value of 3.2, the dimensions of trust in the efficiency of the implementation of the safety system is a “good” category with a mean value of 3. The safety climate overview of PT X has been included into quite well category, within 6 dimensional results is a “good” category, and 1 dimension result is a “bad” category.